Surface water-quality modeling - Chapra, Steven C. (McGraw-Hill, 1997)
The book is organized into seven parts. The first two cover modeling fundamentals, including background material on mathematics, numerical methods, reaction kinetics, diffusion, etc. Part III presents some of the environments commonly encoutered in water-quality modeling: streams, estuaries, lakes, and sediments. The following four parts deal with major water-quality-modeling problems: oxygen/bacteria, eutrophication/temperature, chemistry/pH, and toxics